HUBUNGAN KONDISI RUMAH TIDAK LAYAK HUNI DAN STATUS KEMISKINAN RUMAH TANGGA DI PROVINSI SULAWESI UTARA - Wijayanto, Anton Tri (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract :Many local governments carry out rehabilitation programs for uninhabitable houses with the aim of poverty allevation. However, in implementation, sometimes those programs do not use the proper concept, definition and standard operating procedure. Moreover, the lack of understading about the relationship between the two variables could reduce the effectiveness of those programs. This study aims to exercise the correlation between uninhabitable houses and household poverty statuses in Sulawesi Utara Province by using secondary data from the Socio-economic Household Survey (SUSENAS) conducted by BPS in 2020. The data provide information on 8,350 respondents spreading across all regencies/cities in Sulawesi Utara Province. Using Chi Square Correlation Test Analysis, the uninhabitable status of the household house was correlated with the poverty status of the household. The results of the study found that there is a significant positive correlation between the condition of uninhabitable houses and the poverty status of a household. However, the correlation is relatively quite weak The government can use uninhabitable houses data as the basic data in the rehabilitation program for uninhabitable houses. But it is necessary to carry out deeper verification of households target so that the program can be right on target. Abstrak :Banyak pemerintah daerah melakukan program rehabilitasi rumah tidak layak huni yang bertujuan mengentaskan kemiskinan. Namun dalam pelaksanaannya tidak disertai dengan konsep definisi serta standar operasional yang baku, bahkan tanpa mengetahui kelayakan korelasi antara kedua variabel tersebut. Penelitian ini bertujuan untuk mengetahui korelasi antara rumah tidak layak huni dengan status kemiskinan rumah tangga di Provinsi Sulawesi Utara. Menggunakan data sekunder hasil pendataan SUSENAS,BPS Tahun 2020 sebanyak 8.350 responden yang tersebar diseluruh Kabupaten/kota di Sulawesi Utara. Analisis Uji Korelasi Chi Square dilakukan terhadap variabel komposit status rumah tidak layak huni dengan variabel kemiskinan. Hasil penelitian menyatakan bahwa terdapat korelasi positif yang signifikan meskipun bersifat sangat lemah antara kondisi rumah tidak layak huni dengan status kemiskinan suatu rumah tangga. Pemerintah bisa menggunakan data dasar RTLH ini dalam program rehabilitasi RTLH untuk pengentasan kemiskinan, namun perlu melakukan verifikasi lebih dalam terhadap calon rumah tangga penerima manfaat agar program dapat tepat sasaran.